Optimizing Student's Confidence through Group Counseling Services - Sutiyani, Frikatama Devi; Purwati, P; Sugiyadi, S (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to examine the effectiveness of group counseling with the metaphor technique on increasing affective abilities in students' self-confidence. In this study, the research design used One Group Pretest - Posttest, the design used one group of subjects with one type of treatment, namely the experimental group. The population in this study were junior high school students in Sucen Village, Salam District, Magelang Regency. The number of samples in this study were 6 students. The research subjects were selected by random sampling, which is a sampling technique in which all individuals in the population either individually or jointly are given the same opportunity to be selected as sample members. The data collection instrument used a self-confidence scale. The analytical method in this study uses a parametric paired sample t-test. The results of this study indicate that group counseling with the metaphor technique has a positive effect on increasing affective abilities in students' self-confidence. This is evidenced by the results of the paired sample t-test with a probability value of sig.(2- tailed) 0.001 < 0.05. And with the difference in the average score of the self-confidence questionnaire 23.28% from the pretest and posttest results. This proves that group counseling with the metaphor technique can improve affective abilities in students' selfconfidence.